Antiprotozoal activity of major constituents from the bioactive fraction of Verbesina encelioides. Issue 6 (19th March 2017) - Ezzat, Shahira M; Salama, Maha M; Mahrous, Engy A; Maes, Louis; Pan, Cheol-Ho; Abdel-Sattar, Essam
Abstract: The bioactive petroleum ether fraction of Verbesina encelioides, previously studied by the authors, was chosen for the isolation of antiprotozoal metabolites. Pseudotaraxasterol-3β-acetate (1 ), benzyl 2, 6-dimethoxy benzoate (2 ), 16β-hydroxy-pseudotaraxasterol-3β-palmitate (3 ) and pseudotaraxasterol (4 ), in addition to β -sitosterol glucoside (5 ) and β -sitosterol galactoside (6) were isolated and identified based on one-dimensional and two-dimensional spectral analysis. This is the first report describing(3) and(6) in genus Verbesina . The isolated compounds were tested in vitro against Plasmodium falciparum, Trypanosoma brucei, Trypanosoma cruzi and Leishmania infantum . Cytotoxicity was evaluated on MRC-5 cells. Compound1 showed moderate to weak activity against L. infantum T. brucei and P. falciparum and was inactive against T. cruzi. Compound3 showed moderate activity against L. infantum, compound4 revealed weak activity against T. cruzi, while5 and6 were inactive against all tested protozoa. All compounds were non-cytotoxic. The isolated constituents showed less antiprotozoal activity than the crude fraction. Abstract :